From Urban Space to Everyday Place: Appropriation of Public Leisure Areas in Belo Horizonte, Brazil - Guimarães (Guimaraes), Marcos (Journal of Urban Culture Research, 2025)
The dramatic changes occurred in the organization of cities reverberate in the very individual and interpersonal levels of spatial relationships. This essay approaches the public space by transposing fundamental concepts identified among the urban cultural system to the everyday experience of particular places. This transposition gives an insight into the comprehension of the built environment by exploring links between scales. The referential frame adopted is the set of discourses by Soja (2000) on the post-metropolis. The study cases, two contrasted leisure areas situated in the Brazilian city of Belo Horizonte, are potential spots for the cultural and spatial appropriation of people. They are examined within the city context by means of a more specific literature as well as an empirical research based on ethnographic observational methods. The experiment provides the application of global concepts in very concrete places, where a sharply connection with the processes of urban restructuring is evidenced.